Efektivitas Pembebasan Pajak Pertambahan Nilai Bahan Pakan Ternak yang Diatur dalam Peraturan Menteri Keuangan - Ramadhana, Satria Nur; Rahayu, Eka Ningsih Puji (Universitas Muhammadiyah Metro, 2022)
The purpose of this study was to determine the effectiveness of the exemption of value added tax on animal feed ingredients regulated in the regulation of the minister of finance. This type of research is descriptive research, using a qualitative approach. The technique of collecting data and other information is done by searching, collecting, and studying various kinds of textbooks, laws and regulations and field research. Based on the research conducted by the author, it was found evidence that the purpose of providing facilities in the form of exemption from value added tax on animal feed ingredients was not achieved because the price of animal feed did not change. Exemption of value added tax is actually enjoyed by animal feed entrepreneurs. Therefore, it can be concluded that the provision of value added tax exemption facilities for animal feed raw materials is not effective. The implication of this research is as a regulator evaluation.